Environmental parameters and diversity of diatoms in the Aïn Dalia dam, Northeast of Algeria - KARIMA HERAMZA; CHOUKRI BAROUR; AICHA DJABOURABI; WILLIA KHATI; CHAHINAISE BOUALLAG (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Heramza K, Barour C, Djabourabi A, Khati W, Bouallag C. 2021. Environmental parameters and diversity of diatoms in the Aïn Dalia dam, Northeast of Algeria. Biodiversitas 22: 3633-3644. Diatoms have long been used as biological indicators of the quality of aquatic environments due to their important capacity to respond to environmental change. As this flora has been very little studied in Algeria, the present study aimed to monitor the Spatio-temporal dynamics of diatoms at the Aïn Dalia dam (north-eastern of Algeria) and determine the main abiotic factors contributing to these variations from June 2017 to May 2018 in four selected stations. Our results showed that the waters of Aïn Dalia dam waters vary from moderately (St1 and St3) to significantly polluted (St2 and St4). They host the community of planktonic diatom flora composed of 72 species. The interspecific biodiversity was marked in summer and autumn (57 and 56 species respectively) and in the St4 station (52 species). In terms of abundance, more than 40% of the overall density was found in the St4 station and the fall period. Among the dominant genera, Cyclotella, Thalassiosira, Synedra and Navicula are found in moderately polluted waters, while Nitzschia, Melosira and Surirella in significantly polluted waters. Some environmental parameters, including nutrients (PO43-and NO2-), SM, temperature, dissolved oxygen, and pH played a key role in the functioning and evolution of this lake. Hence, these parameters demonstrated important fluctuations during our study and influenced directly the diatom distribution. These results showed that diatom assemblages are influenced by anthropogenic disturbances, and can be used as indicators of environmental quality.